Effectiveness of an Educational Program on Nurses' Knowledge Toward Early Prediction of Acquired Weakness in The Intensive Care Unit. - Odah, Qassim Jawell; Hattab, Wafaa Abed Ali (Iraqi National Journal of Nursing Specialties, 2023)
Abstract:Objectives: The present study aims to evaluate effectiveness of educational program the nurses' knowledge towards early prediction of acquired weakness in the intensive care unit.Methodology: A pre-experimental study design (comparison of two groups), which was achieved through the pre and post-test method for the study sample through the application of an educational program in the intensive care unit of Al-Zahra Teaching Hospital in Kut city, Wasit Governorate. The study was conducted for the period from 28th April 2022 to 15th August 2022 by selecting a purposive (non-probability) sample for this study. The study sample size was (52) nurses, divided into two groups, each one containing (26) nurse as a control group and a study group. The study group was shown the educational program while the control group was not exposed to the educational program.Results: The results of the study show a clear positive effect on the nurses' knowledge toward the early predictive acquired weakness in the intensive care unit. The study indicated that their high significant differences between the control group and study group, between the pre and post for the study group after presenting them with the educational program.Recommendations: The study recommended to design and construct an educational program for the nursing staff, whereby through the program emphasizing the directed and familiarize with how to deal with acquired weakness in intensive care unit and who reduce complications that result from long stay in ICU.Keys of words: effectiveness educational programs, nurses' knowledge, acquired weakness, intensive care unit